(untitled) (Research, Society and Development, 2021)
The incidence of foodborne outbreaks has gained a high proportion and it is estimated that there are more unreported cases. The aim of the study is to elucidate the epidemiological profile of VAD outbreaks in Brazil based on data from the Integrated Manual for Surveillance, Prevention and Control of Foodborne Diseases. Thus, the study is structured by the presentation of the elements of investigation of VAD, the main categories and production sites of the elements involved in the outbreaks and, finally, the list of the main microorganisms found in the analyzes of the reported outbreaks and their health effects human. This is a descriptive, epidemiological, documentary study with a quantitative approach and with the variables analyzed: food and outbreaks 2016 and 2017, signs and symptoms 2016 and 2017, epidemiological profile of patients in 2016 and 2017, outbreaks and regions of Brazil 2016 and 2017 and Micro-organisms transmitted to food 2016 and 2017. When analyzing the place of food production, it was found that the outbreaks occur mostly in homes and commercial establishments. Thus, the need for further studies and public alternatives to change the population’s behavior and the inclusion of nutritionists in commercial and industrial establishments is evident.